Poverty Map sebagai Potret Ketimpangan Pendapatan Area Kecil di Kota Yogyakarta - Widyawati, Dewi; Muchlisoh, Siti (UI Scholars Hub, 2022)
Inequality occurs in the process of economic development along with differences in the natural resources and infrastructure owned by each region. Income inequality reduction programs require accurate data collection and have to reach the smallest areas. This study discusses the application of the Elbers, Lanjouw, and Lanjouw (ELL) and Counterfactual methods to obtain estimates of income inequality indicators at the sub-district and village levels in the Kota Yogyakarta and map them in the form of a poverty map. The data used are Population Census 2010, SUSENAS (2010 and 2018), PODES (2011 and 2018), as well as other BPS publications. The results showed that the estimator of income inequality using the ELL method has a smaller RSE value than the direct estimation results. Poverty Map presents a snap-shot of the distribution of the level of inequality in a relatively heterogeneous small area.